Once daily ceftriaxone and gentamicin for the treatment of febrile neutropenia. Issue 2 (1st February 1999) - Tomlinson, Richard J; Ronghe, Milind; Goodbourne, Colin; Price, Christine; Lilleyman, John S; Das, Satya; Saha, Vaskar
Abstract : AIMS: To evaluate the pharmacokinetics of once daily (OD) gentamicin and its effectiveness as part of an OD regimen for the empirical treatment of febrile neutropenia in children with cancer. SUBJECTS: 59 children aged 6 months to 16 years (mean (SD) 5.7 (4) years) with febrile neutropenia (neutrophil count < 0.5 × 10 9 /l) after chemotherapy. METHODS: Over one year, 113 febrile neutropenic episodes were treated empirically with an OD antibiotic regimen of ceftriaxone (80 mg/kg; maximum 4 g) and gentamicin (7 mg/kg; infused over 60 minutes, no maximum). The patients were assessed after 48 hours. RESULTS: 86 of the 113 episodes settled with the first line antibiotic regimen. In 29 episodes, blood cultures identified a causative bacterial pathogen; for 17 of these, the first line antibiotic regimen was adequate; in four episodes, although the episode settled, ceftriaxone was replaced by a more appropriate antibiotic and OD gentamicin was continued; in the remaining eight episodes, a glycopeptide antibiotic was deemed necessary. There was no failure of treatment in organisms sensitive to gentamicin, including Pseudomonas aeruginosa . In 27 episodes (24%), resolution was obtained by the empirical introduction of a second line regimen of ceftazidime and a glycopeptide antibiotic, and/or amphotericin. Gentamicin concentrations were measured in 110 episodes and they were all below the 24 hour line indicating that there was no need to change the dosing interval. In two episodes (2%), serum creatinine rose transiently by more than 50% of the baseline concentration. Although there was no vestibular toxicity, three of 30 children who underwent pure tone audiometry reported high frequency hearing loss in one ear. CONCLUSION: OD gentamicin can be used safely and effectively to treat febrile neutropenia in children with cancer. When used for a short period (< 5 days), in children not receiving other nephrotoxic drugs and who have normal serum creatinine, serum gentamicin estimations are unnecessary.